Structural integrity issues of additively manufactured railway components: Progress and challenges. (July 2023) - Wu, Zhengkai; Wu, Shengchuan; Qian, Weijian; Zhang, Haiou; Zhu, Hongbin; Chen, Qingyong; Zhang, Zhenxian; Guo, Feng; Wang, Junsheng; Withers, Philip J.
Highlights: Additive manufacture is a potential technology for advanced railway components. Internal defect is a critical issue to assess the fatigue resistance. Damage tolerance is urgent for the additively manufacture metal components. Abstract: Additive manufacturing (AM) is being increasingly applied in aerospace, healthcare, automotive, and energy fields. Despite good design flexibility, short lead times, and high material utilization, the application of AM by the railway industry is still on the way to engineering, particularly when compared with those of the aerospace and automotive industries. In addition, the role of various AM components in maintenance, optimizing design and production is not fully understood. To this purpose, the advantages and challenges in the utilization of AM technologies are well summarized, and the fatigue assessment aspects of AM components have been emphasized. Potential design methods to tackle the challenges including the well-recognized structural integrity, and future prospects are discussed in details. The findings are not only beneficial to the development of AM for railway engineering, but also for enabling the lightweight design of metallic components, and improving the performance evaluation and safety inspection strategies.